Knowledge and attitudes on first aid and basic life support of pre- and elementary school teachers and parents - Cristian Abelairas-Gómez; Aida Carballo-Fazanes; Santiago Martínez-Isasi; Sergio López-García; Javier Rico-Díaz; Antonio Rodríguez-Núñez (Elsevier, 2020)
Objective: The aim of this study was to evaluate the knowledge of first aid (FA) of primary and pre-school teachers and the parents of children in these education stages. Methods: A questionnaire already used in previous publications was employed and consisted of 4 sections: (1) general information; (2) assessment of FA knowledge; (3) questions about FA, and (4) attitudes about FA. The questionnaire was sent by e-mail in Google Forms format to different education centres of the Autonomous Community of Galicia. The centres were asked to send them to the school staff and parents of the pupils so that they could be completed. Results: A total of 470 questionnaires were analysed (177 teachers; 242 parents and 51 teachers with children). More than half (268, 57%) of the participants stated to have knowledge of FA. In the case of the school teachers, associations were found between having undertaken some kind of FA training and teaching these contents (P = .008). Only 4 participants were able to put in the correct order the steps of the basic life support sequence, and nobody answered correctly all the questions about cardiopulmonary resuscitation. More than 95% of the sample were in favour to include FA in the school curriculum and in the study plans of university degrees aimed to train school/high school teachers. Conclusions: The majority of teachers and parents had training in FA, although they did not respond correctly to the questions related to basic life support. The inclusion of these contents in school curricula would be recommendable, but it would require training of the teaching staff beforehand. The inclusion of these contents in university study plans should be a measure to take into account. Resumen: Objetivo: El objetivo de este estudio fue evaluar los conocimientos en primeros auxilios (PP. AA.) de profesorado de educación infantil y primaria y de progenitores de niños en estas etapas educativas. Métodos: Se utilizó un cuestionario ya usado en publicaciones previas compuesto por 4 secciones: 1) información general; 2) valoración de los conocimientos en PP. AA.; 3) preguntas sobre PP. AA., y 4) consideraciones sobre los PP. AA. El cuestionario fue enviado a diferentes centros educativos de la Comunidad Autónoma de Galicia vía correo electrónico en formato Google Formularios. Se les solicitaba a los centros que los enviasen al claustro de profesores y progenitores del alumnado para su cumplimentación. Resultados: El número total de cuestionarios analizados fue 470 (177 docentes; 242 progenitores; 51 docentes con hijos). Doscientos sesenta y ocho (57%) participantes afirmaron poseer conocimientos en PP. AA. En el caso de los docentes, se encontró asociación entre tener formación e impartir estos contenidos en el aula (p = 0,008). Solamente 4 participantes supieron ordenar la secuencia de soporte vital básico y ninguno respondió correctamente a a todas las preguntas sobre reanimación cardiopulmonar. Más del 95% de la muestra consideraba necesario incluir formación en PP. AA. En el currículo escolar y en los planes de estudios de carreras destinadas a formar al profesorado. Conclusiones: La mayoría de los docentes y progenitores tenían formación en PP. AA., aunque no supieron responder correctamente a preguntas relacionadas con el soporte vital básico. Sería recomendable la inclusión de estos contenidos en los currículos escolares, pero para ello sería preciso formar previamente al profesorado. La inclusión de estos contenidos en los planes de estudios universitarios debería ser una medida a tener en cuenta.